Effect of corporate governance on expropriation practices with family ownership as moderation variable - Rettob, Gladys Bella Novenna; Subekti, Imam; Mardiati, Endang (International research journal of management, IT and social sciences, 2021)
The practice of expropriation is one of the accounting frauds committed by controlling shareholders because of their control rights that exceed cash flow rights. This study aims to examine and analyze the effect of corporate governance on the practice of expropriation and the existence of family ownership as a moderating variable. This research was conducted at companies in all sectors of the Indonesia Stock Exchange. Based on the purposive sampling method, the sample of this study was 78 companies with 312 observations. The research data were analyzed using multiple regression analysis. The results of this study indicate that the practice of expropriation in Indonesia can be minimized by implementing adequate corporate governance. The results of this study also prove that companies whose shareholding structures are dominated by the family will maintain control in the company through their management so that they have an impact on limiting governance practices in reducing expropriation practices.